The Solution:
The given system of equations are:
![\begin{gathered} x-2y=4\ldots eqn(1) \\ 2x+y=-2\ldots eqn(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wf5b0i1ick9p8vhvtvqzgksn28rlz7u40i.png)
We are asked to solve using the Substitution Method.
Step 1:
From eqn(1), we shall find x in terms of y.
![\begin{gathered} x-2y=4 \\ \text{Adding 2y to both sides, we get} \\ x-2y+2y=4+2y \\ x=4+2y\ldots eqn(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mticzvba6mmvpy2xcqu5u1npp1pzop6u84.png)
Putting eqn(3) into eqn(2), we get
![\begin{gathered} 2x+y=-2 \\ \text{Putting 4+2y for x, we get} \\ 2(4+2y)+y=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2n1us9qi0dh6rw1uotw5mf9kweek688rbd.png)
Clearing the brackets, we get
![\begin{gathered} 8+4y+y=-2 \\ \text{Subtracting 8 from both sides, we get} \\ 8-8+4y+y=-2-8 \\ 4y+y=-10 \\ 5y=-10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6u202kmnm5n8gkem8c1rivsjrzm94692gn.png)
Dividing both sides by 5, we get
![\begin{gathered} (5y)/(5)=(-10)/(5) \\ \\ y=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hps8630i97grw3yh9cbomiudnch99qqlw5.png)
Substituting -2 for y in eqn(3), we have
![\begin{gathered} x=4+2y \\ x=4+2(-2) \\ x=4-4=0 \\ \text{ So, the solution is (0,-2)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a3e3xvqxz3oc0sv83yok516t7ra6tc0fkz.png)
Therefore, the correct answer is x=0, y= -2